Highlights of the research project on the awareness and perception of students in the rural areas towards human resource development in Sarawak / Ibrahim Abu Shah ... [et al.] - Syawe, Iris Seh Ling; Abu Shah, Ibrahim; Yap, Yin; Chan, Soon Huat (Biro Penyelidikan dan Perundingan, Institut Teknologi MARA, 1994)
This study investigates the awareness and perception of students in the vast rural and interior areas of Sarawak to establish the socio-economic implication of problems, such as difficulty in accessibility, interior and inadequate school facilities or lack of trained teachers. These differences were compared with those in the urban/sub-urban areas to provide a cross-sectional view of the Forms 3, 4, 5 and 6 students of different ethnicity over nine divisions of Sarawak.